2022
DOI: 10.1111/wvn.12596
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the evidence‐based practice mentorship scale

Abstract: Background Evidence‐based practice (EBP) improves the quality of care, decreases healthcare costs, and improves job satisfaction. However, nurses and other clinicians, as well as their institutions, struggle to consistently implement EBP. The Advancing Research and Clinical practice through close Collaboration (ARCC©) Model established that a cadre of EBP mentors is key to improving EBP knowledge, beliefs, competency, and implementation in clinicians. Yet, there has not been a valid and reliable measure of EBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several research studies have found that EBP mentors are critical for embedding and sustaining organizational EBP efforts (Cullen et al, 2020; Melnyk et al, 2022; Wang et al, 2021). Melnyk et al (2022) recently developed an instrument to measure nurses' perception of the availability of EBP mentorship and support, a valuable addition to the assessment of institutional EBP culture (Melnyk et al, 2022). EBP mentors have the in‐depth knowledge, skills, and competencies needed to nurture the structures and cultures necessary for EBP to flourish (Melnyk et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research studies have found that EBP mentors are critical for embedding and sustaining organizational EBP efforts (Cullen et al, 2020; Melnyk et al, 2022; Wang et al, 2021). Melnyk et al (2022) recently developed an instrument to measure nurses' perception of the availability of EBP mentorship and support, a valuable addition to the assessment of institutional EBP culture (Melnyk et al, 2022). EBP mentors have the in‐depth knowledge, skills, and competencies needed to nurture the structures and cultures necessary for EBP to flourish (Melnyk et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Melnyk et al (2022) recently developed an instrument to measure nurses' perception of the availability of EBP mentorship and support, a valuable addition to the assessment of institutional EBP culture (Melnyk et al, 2022). EBP mentors have the in‐depth knowledge, skills, and competencies needed to nurture the structures and cultures necessary for EBP to flourish (Melnyk et al, 2022). EBP mentors and change champions are but one strategy supporting these efforts (Cullen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation